Essays on development and development cooperation - Ole Winckler Andersen; Lars Engberg-Pedersen; Adam Moe Fejerskov; Mikkel Funder; Abel Gwaindepi; Esbern Friis-Hansen; Marie Kolling; Rasmus Hundsbæk Pedersen; Finn Stepputat; Ole Therkildsen (Danish Institute for International Studies (DIIS), 2025)
After earlier strategies for Denmark's development cooperation from 1993, 2000, 2010, 2012 and 2017, the latest strategy, The World We Share, from 2021 now expires, and a new is accordingly(?) needed. The parliament will start negotiating the strategy in May 2025. One may fear that it will be in line with earlier strategies focussing on Danish concerns in the short run and so broad that the government can do whatever it finds useful. There are, however, many reasons for rethinking development cooperation thoroughly, and the latest events - the de facto abolishment of USAID and the significant cuts in several European countries - do not reduce the need for reflection. Written before these events, this DIIS Working Paper contains a number of essays by DIIS researchers who reflect on the needs within their field of specialisation. Thus, the collection of essays covers a broad range of topics. Cutting across the essays there is an attempt to look for opportunities and ways forward. Although the world may appear bleak, there is also room-for-manoeuvre, and even a small country like Denmark can take initiatives that will help people suffering from poverty and a world suffering from instability.
Keywords: 330